2011
DOI: 10.1002/pen.21974
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite nanoclay filler effects on electrical conductivity, thermal and mechanical properties of epoxy‐based nanocomposites

Abstract: Epoxy-based nanocomposites with 2, 5, and 7 wt% of montmorillonite (MMT) nanoclay were prepared using high shear melt mixing technique. The microstructural features of the nanocomposites were investigated by transmission electron microscopy (TEM). The thermal and mechanical properties were measured using differential scanning calorimetry (DSC), thermogravimetric analyzer (TGA), and dynamic mechanical analyzer (DMA). Further, the effect of voltage, temperature, seawater aging on the electrical conductivity (r D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…15,16 Mechanical interlocking prevents movement of the polymer chains and plays a role in enhancing the mechanical properties of HDPE. 17 When 1.0 and 2.0 wt.% nanoclay-reinforced HDPE were compared, both tensile strength and secant modulus of 3.0, 4.0, and 5.0 wt.% nanoclay-reinforced HDPE decreased. The reason for this is thought to be interface inconsonance between the nanoclay and HDPE polymer chains at a molecular level.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…15,16 Mechanical interlocking prevents movement of the polymer chains and plays a role in enhancing the mechanical properties of HDPE. 17 When 1.0 and 2.0 wt.% nanoclay-reinforced HDPE were compared, both tensile strength and secant modulus of 3.0, 4.0, and 5.0 wt.% nanoclay-reinforced HDPE decreased. The reason for this is thought to be interface inconsonance between the nanoclay and HDPE polymer chains at a molecular level.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…11 In contrast, a reduction in tensile strength of NC-modified polymers has been claimed in previous studies. 26,39,67,68 The presence of microvoids-proportional to the clay content due to an increased dispersion viscosity-and agglomerated NC particles have been reported to be the main reasons for a reduction in strength. The manufacturing process itself might be another causal factor for the differences, as the specified material properties for neat VE and EP are not properly matching either as indicated by the materials properties in Table 1.…”
Section: Effect On the Static Mechanical Propertiesmentioning
confidence: 99%
“…Layered aluminum silicate (hereafter called nanoclay) offers intriguing properties such as natural abundance with environmental stability, a platelet-like geometry with a high aspect ratio, and well-established intercalation chemistry compared with other silicate materials. , Recently, Vellakkat et al reported the dielectric constant and transport mechanism of a novel intercalated nanoclay/PANI composite for industrial purposes prepared by a mechanochemical method. Rashmi et al reported the effect of the nanoclay loading on the conductivity of epoxy-clay-based nanocomposites, where a nanoclay loading of 2 wt % gave the highest conductivity, which was achieved as a result of the subsequent increase in the volume fraction of the entire interfacial region coupled with enhanced free charge carriers. Similarly, Basak et al reported because of its large abundance, environmentally friendliness, and intercalation chemistry, nanoclay can be used in various polymer nanocomposites as a reinforcement phase even at lower loadings of clay, which offers a wide array of property improvement.…”
Section: Introductionmentioning
confidence: 99%